Role of calcium-sensing receptor, Galectin-3, Cyclin D1, and Ki-67 immunohistochemistry to favor in the diagnosis of parathyroid carcinoma - Nuran Sungu; Hayriye Tatli Dogan; Aydan Kiliçarslan; Mehmet Kiliç; Sefika Polat; Mehmet Tokaç; Soner Akbaba; Ömer Parlak; Serdar Balci; Betül Ögüt; Bekir Çakir (Wolters Kluwer Medknow Publications, 2018)
Background: As histopathological findings of parathyroid carcinoma are not certain, the diagnosis of tumors with degenerative changes may be difficult. In these cases, immunohistochemical markers are beneficial. We aimed to research the acceptability of calcium-sensing receptor (CaSR), Galactin-3, Cyclin D1, and Ki-67 as helpful markers in parathyroid tumors in cases which are difficult to diagnose. Materials and Methods: Those cases who had been diagnosed with atypical parathyroid adenoma and parathyroid carcinoma between 2010 and 2015 were reevaluated. İmmunohistochemical markers were applied to this cases. Results: About 21 cases were parathyroid adenoma, 14 were atypical adenoma, and 10 cases were parathyroid carcinoma. According to the immunohistochemical results, global loss of CaSR staining was seen in 50% (5/10) of the patients with carcinoma while there was no loss of staining in those with parathyroid adenoma (P = 0,001). Global loss of CaSR staining was found in only one out of 14 cases with atypical adenoma. The expression of Galactin-3 was found to be positive in 40% (4/10) of carcinoma cases, 71.4% (10/14) of those with atypical adenoma, and 14.3% (3/21) of those with adenoma (P = 0,002). Cyclin D1 expression was determined to be positive in 70% (7/10) of patients with carcinoma, 71.4% (10/14) of atypical adenoma cases, and 23.8% (5/21) of those with adenoma. The Ki-67 proliferation index was seen to be above 5% in 50% (5/10) of carcinoma cases and 35,7% (5/14) of those with atypical adenoma. Conclusion: In these studies, it has been emphasized that the global loss of CaSR staining was used as a negative marker in the diagnosis of carcinoma. In this study, we have also confirmed that the global loss of CaSR staining is a useful marker to determine potential increased malignancy.